EVALUATION OF QUALITY OF LIFE OF PARENTS AND CAREGIVERS OF ASTHMATIC CHILDREN - Roncada, Cristian (Rev Paul Pediatr, 2018)
OBJECTIVE: To evaluate and compare the levels of quality of life of parents/caregivers of children with and without diagnosis of asthma. METHODS: Parents of children with asthma (asthma group) undergoing outpatient care and parents of children without asthma or asthma in remission (control group) were selected from public schools. They answered a questionnaire about quality of life (The World Health Organization Quality of Life- WHOQOL-BREF), previously validated for the study population. Domains (physical, psychological, social relations, environment and total score) were compared between groups, as well as the levels of correlation of self-perceived quality of life and satisfaction with health. RESULTS: 101 parents/caregivers were included in the sample, that is, 50 (49.5%) parents of asthmatic children and 51 (50.5%) in the control group. Most parents included in the sample were females (n=89; 88.1%), with mean age of 33.5±10.4 years. When assessing quality of life, the overall score of domains was considered satisfactory, both in general evaluation (68.6±13.4) and in each group (asthma: 62.8±10.7; control: 74.3±13.4; p-value<0.001). Comparison of asthma and control groups showed significant differences in total score and in scores of all domains (p<0.001). CONCLUSIONS: Parents/caregiversof children with asthma have a lower quality of life compared to parents/caregivers of healthy children.